El Salvador : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for El Salvador. (IMF Staff Country Reports; Country Report ;, 2008)
In 2007, imports of consumer, intermediate, and capital goods grew at annual rates slightly exceeding 10 percent. Export growth lagged behind that of imports, as buoyant nontraditional exports, rising at a 16 percent annual rate, were offset by stagnant exports of the maquila sector. In particular, the discussions centered on (i) spillovers from the United States to El Salvador and the associated risks; (ii) the short-term fiscal stance and its consistency with medium-term fiscal objectives; and (iii) the internationalization of the Salvadoran banking system.